MULTIDISCIPLINARY APPROACH TO PATIENT CARE: PERSPECTIVES FROM NURSING, RADIOLOGY, PARAMEDICINE, AND PHARMACY PROFESSIONALS IN SAUDI ARABIA - Mateb Owaid Somidan Alanazi, Khalid Tharwi M Alshammari, Anwar Hamad Saleh Aldhafeeri, Abdullah Mouhan Alfadhli, Mohammed Abdullah Albadrani, Abdullateef Aiyed Aldhefeeri. (Chelonian Research Foundation, 2022)
Background: Multidisciplinary collaboration is essential for providing comprehensive, high-quality patient care. However, limited research has explored the perspectives and experiences of healthcare professionals from different disciplines in Saudi Arabia regarding collaborative practice. Objective: This study aimed to investigate the perceptions, barriers, and facilitators of multidisciplinary collaboration among nursing, radiology, paramedicine, and pharmacy professionals in Saudi Arabia. Methods: A qualitative descriptive design was used. Semi-structured interviews were conducted with a purposive sample of 20 healthcare professionals (5 nurses, 5 radiological technologists, 5 paramedics, and 5 pharmacists) working in various healthcare settings in Riyadh, Saudi Arabia. Thematic analysis was performed to identify key themes and subthemes. Results: Four main themes emerged: 1) understanding of multidisciplinary collaboration, 2) benefits of multidisciplinary collaboration, 3) challenges to multidisciplinary collaboration, and 4) strategies to enhance multidisciplinary collaboration. Participants recognized the importance of collaboration for improving patient outcomes, but identified several barriers such as communication issues, role ambiguity, hierarchical structures, and lack of interprofessional education. Strategies to promote collaboration included fostering open communication, clarifying roles and responsibilities, providing interprofessional training opportunities, and leadership support. Conclusion: Multidisciplinary collaboration is valued by healthcare professionals in Saudi Arabia, but various challenges hinder its effective implementation. Addressing these barriers through interprofessional education, communication skills training, and organizational support can foster a collaborative practice environment and ultimately improve patient care quality and outcomes. Keywords: interprofessional collaboration; multidisciplinary teams; healthcare professionals; qualitative research; Saudi Arabia